2017
DOI: 10.1016/j.ins.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

ORFEL: Efficient detection of defamation or illegitimate promotion in online recommendation

Abstract: What if a successful company starts to receive a torrent of low-valued (one or two stars) recommendations in its mobile apps from multiple users within a short (say one month) period of time? Is it legitimate evidence that the apps have lost in quality, or an intentional plan (via lockstep behavior) to steal market share through defamation? In the case of a systematic attack to one's reputation, it might not be possible to manually discern between legitimate and fraudulent interaction within the huge universe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Auter and Fine [29] found that attack advertising on social media sometimes can act as an important measure used by a politician to compete with his opponent on an election campaign. Gimenes et al [30] found that the low-valued user-product recommendation in some mobile apps can lead to the security problems of illegitimate promotion, and proposed the method of using vertex-centric asynchronous parallel processing of bipartite graphs to detect illegitimate promotion. Zhang [31] proposed the deep learning algorithms based on lexical features which can be used for classifying and visualizing the advertisements to detect the malicious advertisements.…”
Section: Related Workmentioning
confidence: 99%
“…Auter and Fine [29] found that attack advertising on social media sometimes can act as an important measure used by a politician to compete with his opponent on an election campaign. Gimenes et al [30] found that the low-valued user-product recommendation in some mobile apps can lead to the security problems of illegitimate promotion, and proposed the method of using vertex-centric asynchronous parallel processing of bipartite graphs to detect illegitimate promotion. Zhang [31] proposed the deep learning algorithms based on lexical features which can be used for classifying and visualizing the advertisements to detect the malicious advertisements.…”
Section: Related Workmentioning
confidence: 99%
“…O trabalho Online-Recommendation Fraud Excluder (ORFEL) 2 (Gimenes et al, 2016) foi desenvolvido para tratar o problema de detecção de fraudes em redes de recomendação. Nestas redes,é possível criar usuários falsos para difamar ou promover produtos por meio de recomendações eletrônicas ilegítimas ao longo do tempo, o que dificulta sobremaneira o problema.…”
Section: Identificação De Fraudesunclassified
“…Experiments of scalability over the number of seeds.Source:Gimenes, Cordeiro and Rodrigues-Jr (2016).…”
mentioning
confidence: 99%